The Jasmine Plant Growth Effect Supplemented with Liquid Organic Fertilizer from Banana Peels - Selly, Rini; Panjaitan, Angel Shylvia; Br. Gurusinga,, Dinda Natalisa; Khairunissa, Dira; Manalu, Santa Maria; Rahmah, Siti (Indonesian Journal of Chemical Science and Technology (IJCST), 2023)
Liquid organic fertilizer (LOF) is a solution resulting from the decomposition of organic matter originating from plant residues, agro-industrial waste, animal waste, and human waste containing more than one nutrient. LOF can be made from liquid organic matter (liquid organic waste), by composting and providing composting activators so that a LOF that is stable and contains complete nutrients can be produced. The use of LOF has the advantage that although it is often used it does not damage the soil and plants, the use of organic waste as fertilizer can help improve soil structure and quality, because it contains nutrients and other organic matter. The process of adding different fertilizers to the plants for 10 days showed that there were different height changes for each plant. With only water, the plants only reach 0.1 cm difference in 7 days. The plants that were given LOF and NPK (Chemical Fertilizer) gained height in only 4 days with heights 15.6 cm and 16 cm respectively. The growth percentage between LOF and NPK showed a significant difference in 4 days with 0.6% and 3.2 % respectively.